FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MINAT KUNJUNGAN ULANG PASIEN RAWAT JALAN DI WILAYAH KERJA PUSKESMAS TALANG BANJAR KOTA JAMBI - aini, muthma; Noerjoedianto, Dwi; Mekarisce, Arnild Augina (LPPM Universitas Awal Bros, 2025)
Repeat visit intention is an essential indicator of service continuity in primary healthcare facilities, reflecting patient perceptions of service quality, satisfaction, accessibility, and overall experience. The outpatient visit rate at Talang Banjar Health Center has shown fluctuations, indicating the need to identify factors influencing repeat visit interest. This quantitative study used a cross-sectional design with 106 respondents selected through accidental sampling. Data were collected using structured questionnaires and analyzed using the Chi-square test to examine relationships between service quality, patient satisfaction, accessibility, waiting time, and repeat visit intention. The findings showed that 63.2% of respondents had an interest in returning, while 36,8% did not. Significant relationships were found between repeat visit intention and service quality (p = 0.006; PR = 3.034), patient satisfaction (p = 0.001; PR = 4.348), accessibility (p = 0.005; PR = 3.100). and waiting time (p = 0.001 ; PR = 3.912). These results indicate that improving service quality, enhancing patient satisfaction, accessibility, and waiting time are crucial to strengthening patient interest in returning to the health center. Strengthening these aspects may support better service continuity in primary healthcare settings.